Survival Outcomes Between Clear Cell and Non-Clear Cell Epithelial Ovarian Cancer - Wasanai Jermsirisakpong; Suphet Tuipae (The Royal Thai College of Obstetricians and Gynaecologists, 2013)
Objective: To compare the 5-year survival rates of women with clear cell (CCC) versus those with non-clear cell (non-CCC) epithelial ovarian cancer.Materials and Methods: Retrospective study was performed on patients with epithelial ovarian cancer who had undergone treatment at Rajavithi Hospital from January 1995 to December 2006. Five-year survival rate was compared between the clear cell (n=196) and non-clear cell (n= 304) epithelial ovarian cancer. Result:The mean age of patients with CCC was 49.7 years compared to 49.1 years for non-CCC group. Of 196 patients with CCC, 99 patients (50.5%) were in stage I. Of 304 patients with non-CCC, 100 patients (32.9%) were in stage I. Most of patients with CCC had optimal surgery and received paclitaxel and platinum (PT) regimen whereas most of patients with non-CCC had optimal surgery and received chemotherapy other than PT regimen. Median follow up time was 46.0 months. The 5-year survival rates were 60.4% for patients with clear cell and 63.8% for patients with non-clear cell group (p<0.001). Conclusion: The overall 5-year survival rate of patients with CCC was significantly poorer than non-CCC epithelial ovarian cancer (60.4% VS 63.8%).